The Food52 cookbook : 140 winning recipes from exceptional home cooks - Hesser, Amanda (William Morrow, 2011)
"The best recipes come from talented home cooks! On Food52.com (named "Best of the Web" by Saveur), bestselling author Amanda Hesser and food writer Merrill Stubbs have curated the first-ever online community cookbook, the basis for this gorgeous full-color book filled with more than 125 delicious seasonal recipes from the country's most inventive home cooks"--